Studying the Effect of Hydroalcoholic Extract of Teucrium polium L. Leaves on Antioxidant Activity and Lipid Profile Alterations - Nargesi, Shahin (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Antioxidants are the most important factors preventing oxidative stress and scavenging free radicals. Nowadays, natural antioxidant compounds are highly important in prevention of cardiovascular diseases. In this study, we have investigated the effect of hydroalcoholic extract of Teucrium polium L. leaves (HETPL) on enzymes related to antioxidant activity and lipid profile alterations in rats. Materials and Method: Male Wistar rats were divided into four equal groups for 8 weeks: Experimental groups of 1 and 2, which had a normal diet and high cholesterol diet (2%) respectively, and experimental groups of 3 and 4, which were treated with high cholesterol diet (2%) with HETPL at doses of 85 and 170 mg/kg, respectively. The levels of malondialdehyde (MDA) and plasma superoxide dismutase (SOD) of red blood cell (RBC) and lipid profile were measured at the beginning and at the end of the study. Results: The levels of SOD in RBC and plasma MDA in the experimental Group 2 had a significant increase compared to the experimental Group 1 (P < 0.001). The level of these two enzymes in the experimental groups of 3 and 4 was significantly lower than the experimental Group 2 (SOD by P < 0.05 and P < 0.001 and MDA by P < 0.01 and P < 0.001, respectively). The mean serum high-density lipoprotein cholesterol level in experimental Groups 1 and 4 at the end of study had no significant alteration compared to the beginning of the study, but in the experimental groups of 2 and 3, a significant decrease was observed at the end of the study than the beginning of the study (P < 0.001 and P < 0.01, respectively). Mean serum levels of triglyceride (TG), cholesterol, and low-density lipoprotein cholesterol (LDL-c) in experimental Groups 2 (LDL-c and cholesterol: P < 0.001 and TG: P < 0.01) and 3 (P < 0.01) significantly increased compared to the beginning of the study. Conclusion: We conclude that T. polium can play an important role in preventing cardiovascular diseases caused by oxidative stress through its antioxidant and hypolipidemic activities.